Influencia del tamaño de bellota y del régimen de riego en la calidad de planta de alcornoque cultivada en vivero - Pardos Mínguez, M.; Cañellas, I.; Bachiller, A. (II Congreso Forestal Español, 1997)
The effect of three acorn sizes (small, medium and large, 2.5, 5 and 8.8 g mean fresh weight, respectively) and two irrigation regimes (Rl=2R2) in the growth of cork oak containerized (Forest Pot 300) seedlings was studied. The seedlings were grown in the nursery for one year.The results showed the influence of the acorn size on caliper, root volume, shoot, root and acorn dry weights, leaf area, leaf weight ratio (L WR), leaf area ratio (LAR), midday water potential and transpiration. Irrigation was statistically significant for height and totalleaf area. Water potential reached less than -2 MPa in July. This fact reveals the adaptation of the species to drought.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español
Keywords: acorn size; irrigation; Quercus suber; seedling quality